The shaping of life : the generation of biological pattern - Harrison, Lionel G. (Cambridge : Cambridge University Press, 2011)
'Biological development, how organisms acquire their form, is one of the great frontiers in science. While a vast knowledge of the molecules involved in development has been gained in recent decades, big questions remain on the molecular organization and physics that shape cells, tissues and organisms. Physical scientists and biologists traditionally have very different backgrounds and perspectives, yet some of the fundamental questions in developmental biology will only be answered by combining expertise from a range of disciplines. This book is a personal account by Professor Lionel Harrison of an interdisciplinary approach to studying biological pattern formation. It articulates the power of studying dynamics in development: that to understand how an organism is made we must not only know the structure of its molecules; we must also understand how they interact and how fast they do so'--
Keywords: Pattern formation (Biology).; Morphogenesis; Developmental biology